Microbial Eukaryotes Associated With Sediments in Deep-Sea Cold Seeps - Zhang, Yue; Huang, Ning; Wang, Minxiao; Liu, Hongbin; Jing, Hongmei (Frontiers in Microbiology, 2021)
Microbial eukaryotes are key components of the marine food web, but their distribution in deep-sea chemosynthetic ecosystems has not been well studied. Here, high-throughput sequencing of the 18S rRNA gene and network analysis were applied to investigate the diversity, distribution and potential relationships between microbial eukaryotes in samples collected from two cold seeps and one trough in the northern South China Sea. SAR (i.e., Stramenopiles, Alveolata, and Rhizaria) was the predominant group in all the samples, and it was highly affiliated to genotypes with potential symbiotic and parasitic strategies identified from other deep-sea extreme environments (e.g., oxygen deficient zones, bathypelagic waters, and hydrothermal vents). Our findings indicated that specialized lineages of deep-sea microbial eukaryotes exist in chemosynthetic cold seeps, where microbial eukaryotes affiliated with parasitic/symbiotic taxa were prevalent in the community. The biogeographic pattern of the total community was best represented by the intermediate operational taxonomic unit (OTU) category, whose relative abundance ranged 0.01–1% within a sample, and the communities of the two cold seeps were distinct from the trough, which suggests that geographical proximity has no critical impact on the distribution of deep-sea microbial eukaryotes. Overall, this study has laid the foundations for future investigations regarding the ecological function and in situ trophic relationships of microbial eukaryotes in deep-sea ecosystems.